Modeling the biomechanics of cells on microcarriers in a stirred-tank bioreactor: an ABM-CFD coupling approach - Cantarero-Rivera, Fernando; Camphuijsen, Jaro; Potter, Greg; Clark, Chris; Chen, Jiajia; Kahan, Simon; Aguilar, Boris (Frontiers in Food Science and Technology, 2024)
Highly productive and efficient biomass growth in bioreactors is an essential bioprocess outcome in many industrial applications. Large-scale biomass creation in the cultivated meat industry will be critical given the demand size in the conventional meat and seafood sectors. However, many challenges must be overcome before cultivated meat and seafood become commercially viable, including cost reductions of cell culture media, bioprocess design innovation and optimization, and scaling up in the longer term. Computational modeling and simulation can help to address many of these challenges and can be a far cheaper and faster alternative to performing physical experiments. Computer modeling can also help researchers pinpoint system interactions that matter and guide researchers to identify those parameters that should be changed in later designs for eventual optimization. This work developed a computational model that combines agent-based modeling and computational fluid dynamics to study biomass growth as a function of the operative conditions of stirred-tank bioreactors. The focus was to analyze how the mechanical stress induced by rotor speed can influence the growth of cells attached to spherical microcarriers. The computer simulation results reproduced observations from physical experiments that high rotor speeds reduce cell growth rates and induce cell death under the high mechanical stresses induced at these stir speeds. Moreover, the results suggest that modeling cell death and cell quiescence is required to recapitulate these observations from physical experiments. These simulation outcomes are the first step towards more comprehensive models that, combined with experimental observations, will improve our knowledge of biomass production in bioreactors for cultivated meat and other industries.